Sublethal and chronic effects of pollutants on preshwater fish (Fishing News Books, 1994)
In recent years there has been a greater emphasis on measuring the sublethal effects of pollution on fish. These measurements have been made over the whole range of biological organizations, from the sub-cellular level to changes in community structure. Studies at the lower levels attract considerable scientific interest, but in many cases it has been difficult to interpret the results in terms of predictable harmful effects on individual fish. Conversely, it may be difficult to attribute the effects measured at the higher levels to specific pollutants. This collection of 32 papers presented at a symposium on this subject aims to provide a general picture of current work in this field. This work can form the basis for an integration of the different areas of research in order to give useful advice to fisheries managers and those engaged in pollution prevention and control.